Controllability of rectifiers and three point hysteresis line current control. (October 2016) - Ruiz, Omar F.; Mendoza-Torres, Angelica; Diaz-Diaz, Irwin A.; Cervantes, Ilse; Visairo, Nancy; Nunez, Ciro; Barcenas, Ernesto
Abstract: This paper analyzes the stability and switching controllability properties of a single-phase PWM rectifier and its relationship with parameter uncertainty. Based on this analysis, a switching control strategy is proposed that has as objectives (i) to achieve input current tracking and low current THD (total harmonic distortion) as well as (ii) to regulate the output voltage in spite of perturbations. The proposed control does not require a PWM generation step design. Numerical simulations and experimental tests in a 1 kW prototype demonstrate the effectiveness of the proposed controller and illustrate the limits of system's controllability. Abstract : Graphical abstract: Abstract : Highlights: Controllability of a rectifier at and close to 0 A line currents is analyzed. A current hybrid controller capable to regulate active and reactive power is proposed. The control scheme is multi-objective and robust against parameter uncertainty.